2019
DOI: 10.1111/jgh.14688
|View full text |Cite
|
Sign up to set email alerts
|

Differences in leptin biosynthesis in the stomach and in serum leptin level between men and women

Abstract: Background and Aim:Although the stomach has been identified as an important source of leptin, the detailed biosynthesis sites of leptin in human gastrointestinal tract have not been fully elucidated. The study objective was to compare leptin distribution and expression in the stomach and its serum level between healthy men and women. Methods: Nineteen subjects (organ donors; 10 men and 9 women) with normal gastric mucosa histology were recruited. Research material contained gastric samples from the cardia, fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, women show greater variability in leptin levels after stress, which indicates that leptin may have different effects on the development of obesity in response to stress depending on gender [41]. The reasons for women's increased susceptibility to AD have not been sufficiently described, but based on the data presented, it can be assumed that one of the reasons may be sex hormones; they cause differential leptin biosynthesis in the stomach and different leptin concentrations in the serum of men and women [42].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, women show greater variability in leptin levels after stress, which indicates that leptin may have different effects on the development of obesity in response to stress depending on gender [41]. The reasons for women's increased susceptibility to AD have not been sufficiently described, but based on the data presented, it can be assumed that one of the reasons may be sex hormones; they cause differential leptin biosynthesis in the stomach and different leptin concentrations in the serum of men and women [42].…”
Section: Discussionmentioning
confidence: 97%
“…This result could be due to the different hormonal profiles existing between both genders, as it is well known that people with obesity have high levels of leptin (34,35). Leptin is present in higher amounts in females than in males (36,37). Therefore, the TC genotype may confer protection against being overweight and obese in men more than women due to hormonal reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin expression is not restricted to adipose tissues; a significant amount of leptin is also produced by the stomach (Kasacka et al, 2019). Bado et al initially discovered that leptin is expressed in rat stomach epithelium (Bado et al, 1998), and other researchers later observed leptin expression in the human stomach as well (Breidert et al, 1999;Sobhani et al, 2000).…”
Section: Stomachmentioning
confidence: 99%